1997
DOI: 10.1016/s0960-9822(06)00259-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release and influx colocalize to the endoplasmic reticulum

Abstract: Intracellular Ca2+ is released from intracellular stores in the endoplasmic reticulum (ER) in response to the second messenger inositol (1,4,5) trisphosphate (InsP3) [1,2]. Then, a poorly understood cellular mechanism, termed capacitative Ca2+ entry, is activated [3,4]; this permits Ca2+ to enter cells through Ca(2+)-selective Ca(2+)-release-activated ion channels [5,6] as well as through less selective store-operated channels [7]. The level of stored Ca2+ is sensed by Ca(2+)-permeant channels in the plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Fig. 3A shows a photomicrograph of the centrifuged oocytes, in which [Ca 2ϩ ] i increases in response to IP 3 and thapsigargin were previously localized to the portion of the oocyte enriched for the ER (17,30). Our observations also showed maximal [Ca 2ϩ ] i increases near this band and were faithfully mimicked by a model based on a diffusible CIF produced only by the ER-enriched band (A.B., P.C., R.B.M., and J.E.K., manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3A shows a photomicrograph of the centrifuged oocytes, in which [Ca 2ϩ ] i increases in response to IP 3 and thapsigargin were previously localized to the portion of the oocyte enriched for the ER (17,30). Our observations also showed maximal [Ca 2ϩ ] i increases near this band and were faithfully mimicked by a model based on a diffusible CIF produced only by the ER-enriched band (A.B., P.C., R.B.M., and J.E.K., manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…Strong arguments against a CIF-based model of SOC activation have been previously raised by some experimental data that were apparently inconsistent with a freely diffusible and long lived messenger traveling from Ca 2ϩ stores to the plasma membranes (19,25,26). Other recent data have provided compelling evidence for the importance of secretory processes and vesicle docking and/or membrane fusion in the activation of store-operated Ca 2ϩ influx (19,27).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of intracellular BAPTA to slow reloading, and of Ba 2+ and Mn 2+ , which are not transported by Ca 2+ pumps, to enter the cytosolic pool following store depletion, was taken as evidence that Ca 2+ entering the cell traverses a narrow gap of cytosol before being actively pumped into the ER [17]. Later studies of Xenopus oocytes, endothelial cells and astrocytes showed that local receptor stimulation evoked Ca 2+ entry (as detected by Cl − channel activation or Ca 2+ -dependent dye signals) that was confined to within 10's to 100's of μm from where Ca 2+ release was thought to occur [18][19][20][21].…”
Section: Communication Between Ca 2+ Stores and The Crac Channel: Locmentioning
confidence: 99%
“…The only available marker for active CRAC channels is the elevated [Ca 2+ ] i microdomains that form near open channels. Several prior studies using Ca 2+ -sensitive dyes have shown that SOCE occurs within 10-100 μM of the ER [19][20][21], but the applied imaging techniques lacked sufficient resolution to pinpoint the relationship between individual influx sites and junctional ER structures. Much higher resolution is possible with TIRF microscopy, which has been used to image Ca 2+ microdomains near voltage-gated Ca 2+ (Ca V ) channels on a submicron scale [67,68].…”
Section: The Dynamic Dyad: Defining the Elementary Unit Of Store-opermentioning
confidence: 99%